The Relationship between Work Stress and Job Oppression among Workers in the Palestinian Public Sector - Masharqa, Odetallah; Musleh, Atieh (Jordan Journal of Business Administration, 2020)
This study aimed to investigate the relationship between work stress and job oppression among workers in the Palestinian public sector. The study sample consisted of 288 male and female employees who were selected in a simple random way. The results showed that there was a strong correlation between work stress and job oppression in the Palestinian public sector. The study came up with a set of recommendations, that include application of functional justice on career paths, especially promotions, in a fair way, as well as clarifying job descriptions and employees’ roles without overlap or duplication.